Incomes policy – Danish style - PEDERSEN, J. (PSL Quarterly Review, 2014)
In the post-war period, under the Bretton Woods regime of fixed exchange rates, Danish economic policy followed a zigzag course. With employment low and balance-of-payments satisfactory, expansionary measures were taken. However, once expansion had gathered momentum the threat of balance-of-payments deficit re-emerged and the process was reversed, resulting in a rise in unemployment. In an attempt to explain this phenomenon the Radical Party proposed the “income-race theory”, suggesting a need for co-ordination of group interests in order to achieve financial stability and a just distribution of income. The present work analyses the income-race theory and the establishment of the Council for Economic Coordination that it inspired. The author considers the Council’s scope, its policy recommendations and their impact in resolving Denmark’s incomes policy problem. JEL: E24, E25, E64, F32